Lowered Plasma Steady-State Levels of Progesterone Combined With Declining Progesterone Levels During the Luteal Phase Predict Peri-Menstrual Syndrome and Its Major Subdomains - Roomruangwong, Chutima; Carvalho, André F.; Comhaire, Frank; Maes, Michael (Frontiers in Psychology, 2019)
Background: It is unknown whether lowered steady state levels of sex hormones coupled with changes in those hormones during the menstrual cycle are associated with premenstrual syndrome (PMS). Objective: To examine associations between levels of progesterone and oestradiol during the menstrual cycle and PMS severity considering different diagnostic criteria for PMS. Methods: Forty women aged 18-45 years with a regular menstrual cycle completed the Daily Record of Severity of Problems (DRSP) for all 28 consecutive days of the menstrual cycle. Blood was sampled at days 7, 14, 21 and 28 to assay oestradiol and progesterone. Results: We developed a new diagnosis of peri-menstrual syndrome, which is characterized by increased DRSP severity in pre and post-menstrual periods and increased scores on the major DRSP dimensions, i.e. depression, physio-somatic symptoms, breast tenderness and appetite, and anxiety. This new diagnosis performed better than classical diagnoses of PMS, including the one presented by the American College of Obstetricians and Gynecologists. Lowered steady state levels of progesterone, when averaged over the menstrual cycle, together with declining progesterone levels during the luteal phase predict severity of peri-menstrual symptoms. Steady state levels of oestradiol and declining oestradiol levels during the cycle are also related to DRSP severity although most of these effects appeared to be mediated by progesterone. Conclusion: A significant increase in menstrual-cycle related symptoms can best be conceptualized as “peri-menstrual syndrome” and may result from “corpus luteum insufficiency”, which may result from suboptimal pre-ovulatory follicular development.